LiInSe2 for Semiconductor Neutron Detectors - Kargar, Alireza; Hong, Huicong; Tower, Joshua; Gueorguiev, Andrey; Kim, Hadong; Cirignano, Leonard; Christian, James F.; Squillante, Michael R.; Shah, Kanai (Frontiers in Physics, 2020)
Lithium Indium Selenide (LiInSe2) is being developed for use as a room temperature semiconductor detector for thermal neutrons The material has been studied for a number of applications including nonlinear optics such as parametric oscillators, as anode material for lithium ion batteries, piezoelectrics, as a scintillation detector material and as a semiconductor detector material. The recent advances of the crystal growth, material processing and detector fabrication have led to semiconductor neutron detectors with up to 100 mm2 active area. The thermal neutron detection sensitivity and gamma rejection ratio (GRR) are comparable to 10atm, He-3 tubes of similar size. Synthesis, crystal growth, detector fabrication, and characterization are discussed.